2006
DOI: 10.1519/r-5050501x.1
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Functional Strength Imbalance of the Lower Extremities

Abstract: The purposes of this study were (a) to determine whether a significant strength imbalance existed between the left and right or dominant (D) and nondominant (ND) legs and (b) to investigate possible correlations among various unilateral and bilateral closed kinetic chain tests, including a field test, and traditional isokinetic dynamometry used to determine strength imbalance. Fourteen Division I collegiate women softball players (20.2 +/- 1.4 years) volunteered to undergo measures of average peak torque for i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
128
2
6

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(158 citation statements)
references
References 17 publications
22
128
2
6
Order By: Relevance
“…The present study revealed trivial non-significant differences right and left limbs in hop performance, however small significant differences were found between D and ND limbs (Table 1), consistent with previous research in university, 12 netball, 13 and softball athletes 27 . Interestingly, the D hopping limb did not always correspond to throwing hand or kicking leg dominance as illustrated in Figures 1; similar to corroborative research.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The present study revealed trivial non-significant differences right and left limbs in hop performance, however small significant differences were found between D and ND limbs (Table 1), consistent with previous research in university, 12 netball, 13 and softball athletes 27 . Interestingly, the D hopping limb did not always correspond to throwing hand or kicking leg dominance as illustrated in Figures 1; similar to corroborative research.…”
Section: Discussionsupporting
confidence: 92%
“…12 This could be due to specific sporting demands which may result in imbalances between limbs, such as the support limb during kicking a football or decelerating limb during a batting stroke and cricket bowl. 27,32 Contrary to expectations, hop imbalances had no detrimental impact on turning and cutting performance (Table 2) which supports the only other study to investigate the impact of between limb asymmetries in unilateral hops on CODS perfor- mance reporting no effect. 10 This outcome is in contrast to previous research which has shown imbalances in unilateral drop jump height and reactive strength associated with slower cutting performance.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Concerning a sport such as baseball or softball, a player may throw or hit with the same side of their body possibly leading to altered ranges of motion and strength asymmetries. [1][2][3] Other sports may require the players to utilize both sides of their body equally, but lengthy playing careers in any sport may result in changes in the range of motion, force producing capabilities, and overall symmetry of one's body.…”
Section: Introductionmentioning
confidence: 99%
“…However, it seems that fatigue of only one of the limbs alters this common command and dissociating the command for both limbs (1) . In practical terms, training, as well as the familiarization to tasks, may reduce the bilateral strength deficit minimizing the asymmetry, especially at fatiguing conditions, in which the control dissociation may modify the overload between limbs, since tasks which present asymmetry between limbs are more prone to injuries during physical performance (30)(31)(32)(33)(34)(35)(36) .…”
Section: Asymmetryindices (%) Dominantmentioning
confidence: 99%